2019
DOI: 10.1007/s10508-018-1329-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Syndemics on HIV-Positive Sexual Minority Men’s Sexual Health Behaviors

Abstract: Objective-This study examined the longitudinal effects of co-occurring psychosocial concerns, or syndemics, on HIV-positive sexual minority men's likelihood of engaging in serodiscordant condomless anal sex (CAS), a health behavior with implications for personal and public health.Methods-Participants included 390 HIV-positive sexual minority men from two prior secondary prevention trials. Over the course of the one-year data collection period (up to 5 observations per participant), participants completed self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Prior studies of syndemic conditions among PLWH showed additive associations with increased odds of ART non-adherence [36][37][38][39][40]43], virological non-suppression [38,40,43] and condomless sex with serodiscordant partners while virally unsuppressed [42,43]. However, these studies have generally treated the outcomes of interest as dichotomous outcomes: ART adherent versus non-adherent [36,39,40,43]; virally suppressed versus unsuppressed [40,43]; and the presence or absence of condomless sex while virally unsuppressed [42,43]. Our study builds upon these past findings by quantifying estimated HIV transmissions longitudinally associated with co-occurring syndemic conditions among a diversity of risk groups of PLWH in care.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Prior studies of syndemic conditions among PLWH showed additive associations with increased odds of ART non-adherence [36][37][38][39][40]43], virological non-suppression [38,40,43] and condomless sex with serodiscordant partners while virally unsuppressed [42,43]. However, these studies have generally treated the outcomes of interest as dichotomous outcomes: ART adherent versus non-adherent [36,39,40,43]; virally suppressed versus unsuppressed [40,43]; and the presence or absence of condomless sex while virally unsuppressed [42,43]. Our study builds upon these past findings by quantifying estimated HIV transmissions longitudinally associated with co-occurring syndemic conditions among a diversity of risk groups of PLWH in care.…”
Section: Discussionmentioning
confidence: 98%
“…Our study adds to growing literature on syndemic conditions and transmission risk behaviour among PLWH. Prior studies of syndemic conditions among PLWH showed additive associations with increased odds of ART non-adherence [36][37][38][39][40]43], virological non-suppression [38,40,43] and condomless sex with serodiscordant partners while virally unsuppressed [42,43]. However, these studies have generally treated the outcomes of interest as dichotomous outcomes: ART adherent versus non-adherent [36,39,40,43]; virally suppressed versus unsuppressed [40,43]; and the presence or absence of condomless sex while virally unsuppressed [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rates of HIV-testing are higher amongst Latina/o/x individuals and LSMM compared to their White heterosexual counterparts [ 11 ], people identifying as Latina/o/x are still at higher risk of late HIV diagnoses [ 12 ] and being undiagnosed [ 13 ] compared to other racial/ethnic groups. Compounding cultural factors and structural barriers such as lack of health insurance, immigration concerns, and financial hardship may also influence low PrEP uptake and suboptimal HIV-testing frequency amongst people who identify as Latino [ 14 , 15 ]. Therefore, addressing these psychosocial and structural barriers that affect HIV-testing and PrEP engagement among LSMM is a necessary step in working towards the Ending the HIV Epidemic goals and improving HIV-related care for a population facing disparities [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data from a systematic review showed that the median lifetime prevalence of physical intimate partner violence (IPV) was 37.5%, the lifetime sexual IPV was 25.0% among transgender individuals, and they were 1.7 times more likely to experience any IPV compared to cisgender individuals [ 22 ]. According to previous studies, psychosocial problems are linked to the sexual risk behaviors of TGW, such as CAS, thus increasing the risk of HIV acquisition [ 23 , 24 , 25 , 26 , 27 ]. In Lima, Peru, a survey of 328 TGW found an association between physical IPV and condomless receptive anal sex (CRAS) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%